Global existence and asymptotic behavior of solution of second-order nonlinear impulsive differential equations - Denghua Cheng; Jurang Yan (International Journal of Mathematics and Mathematical Sciences)
We consider the global existence and asymptotic behavior of solution of second-order nonlinear impulsive differential equations.